Wheezing-Related Relevant Factors and the Role of Viral Bronchiolitis - Teijeiro, Alvaro; Gómez, R. Maximiliano (Frontiers in Allergy, 2021)
Bronchiolitis is a virus-associated infection of the lower respiratory tract, exhibiting signs and symptoms of airway obstruction. Respiratory Syncytial Virus (RSV) is responsible in most cases; however, different rhinovirus have also been implicated. Specific viruses and time to provoke the first infection, severity of the respiratory condition and atopic status have a determinant role in recurrence of wheezing and asthma development. Genetics, lung function, atopic condition, the role of microbiota and environment, pollution and obesity are considered in the present review. Emergency room visits and hospitalizations because of severe wheezing, and smoking during pregnancy among others, were identified as risk factors for significant morbidity in our population. The approach to personal risk factors (genetics, allergy, and antiviral immunity), environmental exposures (farm, urban, and microbes), and viral virulence provides the opportunity to reduce the morbidity of viral respiratory illnesses and childhood asthma.